ANALISIS BIAYA OPERASIONAL KENDARAAN, ABILITY TO PAY DAN WILLINGNESS TO PAY UNTUK PENENTUAN TARIF BUS TRANS KOETARADJA KORIDOR III - Erlinawati Jalil; Renni Anggraini; Sugiarto Sugiarto (Prodi Magister Teknik Sipil Unsyiah, 2018)
The Government of Aceh through the Department of Transportation develop the transportation system, especially in the means of transportation one of them improve the urban transport system with the mass transit system that is Trans Koetaradja of 6 (six) corridors. Trans Koetaradja transportation is carefully planned so that it has the same direction and destination point and is bound to a predetermined schedule by using transportation cost concept which regulates fare setting so as to provide services for mutual interest, safe, fast, convenient and cheap. This research is conducted to determine the fare of Trans Koetaradja based on vehicle operational cost (VOC), Ability To Pay and Willingness To Pay from its passenger. Primary data were obtained from interviews and field surveys using state preference method in public and student respondents around Corridor III. Sampling was conducted in stratified random sampling to household (home interview survey) with total sample amounted to 110 samples. Data analysis was done by using 3 (three) method of DEPHUB method to calculate VOC, Household Budget Method to get Ability To Pay (ATP) value and perception method to get Willingness To Pay (WTP) value. The results of this study obtained the fare for corridor III based on VOC was Rp. 5,900.00, the general public ATP was Rp. 5,400.00 and student/college student was Rp. 5,200.00, public WTP was Rp. 3.000.00, and student/college student was Rp. 2,800.00